Single Extracellular Vesicle Analysis Using Flow Cytometry for Neurological Disorder Biomarkers - Ali Moussa, Houda Yasmine; Manaph, Nimshitha; Ali, Gowher; Maacha, Selma; Shin, Kyung Chul; Ltaief, Samia M.; Gupta, Vijay; Tong, Yongfeng; Ponraj, Janarthanan; Salloum-Asfar, Salam; Mansour, Said; Al-Shaban, Fouad A.; et al. (Frontiers in Integrative Neuroscience, 2022)
Extracellular vesicles (EVs) are membrane vesicles released from cells to the extracellular space, involved in cell-to-cell communication by the horizontal transfer of biomolecules such as proteins and RNA. Because EVs can cross the blood-brain barrier (BBB), circulating through the bloodstream and reflecting the cell of origin in terms of disease prognosis and severity, the contents of plasma EVs provide non-invasive biomarkers for neurological disorders. However, neuronal EV markers in blood plasma remain unclear. EVs are very heterogeneous in size and contents, thus bulk analyses of heterogeneous plasma EVs using Western blot and ELISA have limited utility. In this study, using flow cytometry to analyze individual neuronal EVs, we show that our plasma EVs isolated by size exclusion chromatography are mainly CD63-positive exosomes of endosomal origin. As a neuronal EV marker, neural cell adhesion molecule (NCAM) is highly enriched in EVs released from induced pluripotent stem cells (iPSCs)-derived cortical neurons and brain organoids. We identified the subpopulations of plasma EVs that contain NCAM using flow cytometry-based individual EV analysis. Our results suggest that plasma NCAM-positive neuronal EVs can be used to discover biomarkers for neurological disorders.